2021
DOI: 10.1177/00034894211041821
|View full text |Cite
|
Sign up to set email alerts
|

Does Prolonged Use of N95 Masks Affect Nasal Mucociliary Clearance? A Single Group Pre-Post Study

Abstract: Objective: It has been shown that prolonged use of face masks results in physiological changes in the nasal cavity. The objective of this study was to examine the effect of prolonged use of face masks on nasal mucociliary clearance (NMC). Methods: A single group pre-post study was conducted to determine the effects of prolonged use of N95 face mask (≥4 hours) on the NMC rates in health care workers. Saccharin transit time (STT) was used to measure the NMC. STT before and after using an N95 mask for at least 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Participants were asked to wear the respective mask for 4 h based on a recent study that found the mean duration of daily face masking during the pandemic to amount to 4.7 h. 10 Moreover, several prior studies assessing potential side effects of face masking used a 4-h wearing time. 24,25 Previous studies found that self-perception of dry mouth increases during continuous face masking. A potential explanation for this observation is a change in breathing pattern from nasal to oral breathing when using face masks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked to wear the respective mask for 4 h based on a recent study that found the mean duration of daily face masking during the pandemic to amount to 4.7 h. 10 Moreover, several prior studies assessing potential side effects of face masking used a 4-h wearing time. 24,25 Previous studies found that self-perception of dry mouth increases during continuous face masking. A potential explanation for this observation is a change in breathing pattern from nasal to oral breathing when using face masks.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to wear the respective mask for 4 h based on a recent study that found the mean duration of daily face masking during the pandemic to amount to 4.7 h 10 . Moreover, several prior studies assessing potential side effects of face masking used a 4‐h wearing time 24,25 …”
Section: Discussionmentioning
confidence: 99%